2016
DOI: 10.1111/nph.14162
|View full text |Cite
|
Sign up to set email alerts
|

PCP‐B class pollen coat proteins are key regulators of the hydration checkpoint in Arabidopsis thaliana pollen–stigma interactions

Abstract: Summary The establishment of pollen–pistil compatibility is strictly regulated by factors derived from both male and female reproductive structures. Highly diverse small cysteine‐rich proteins (CRPs) have been found to play multiple roles in plant reproduction, including the earliest stages of the pollen–stigma interaction. Secreted CRPs found in the pollen coat of members of the Brassicaceae, the pollen coat proteins (PCPs), are emerging as important signalling molecules that regulate the pollen–stigma intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 81 publications
2
74
0
Order By: Relevance
“…Thus, inhibition of the incompatible pollen acts very early, within the first minutes following stigma contact, blocking pollen hydration. As previously described, hydration appears as the first check point controlling pollen rejection in SI species with dry stigma (Zuberi and Dickinson, 1985; Dickinson, 1995; Samuel et al , 2009; Hiroi et al , 2013; Safavian and Goring, 2013; Wang et al , 2016). In this study, the hydration threshold required to trigger germination was found to correspond to a pollen L/W ratio below 1.4.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Thus, inhibition of the incompatible pollen acts very early, within the first minutes following stigma contact, blocking pollen hydration. As previously described, hydration appears as the first check point controlling pollen rejection in SI species with dry stigma (Zuberi and Dickinson, 1985; Dickinson, 1995; Samuel et al , 2009; Hiroi et al , 2013; Safavian and Goring, 2013; Wang et al , 2016). In this study, the hydration threshold required to trigger germination was found to correspond to a pollen L/W ratio below 1.4.…”
Section: Discussionmentioning
confidence: 64%
“…5C). We calculated the slopes of the hydration curves by linear regression, as previously described (Wang et al , 2016), and found that early and intermediate germinating pollen grains had the highest hydration rates compared with late and non germinating pollen grains (Fig 5C). Non germinating pollen exhibited a very slow hydration rate (slope – 0.043) associated with a poor water uptake at 10 min, deduced from the high pollen ratio (mean of 1.77).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, both of these secreted glycoproteins were also demonstrated to bind to small Brassica class-A pollen coat proteins (PCPs; Doughty et al 1993;Hiscock et al 1995;Takayama et al 2000). More recently, class-B PCPs were demonstrated to be required for pollen adhesion and hydration on stigmas as pollen grains from a triple pcp-b mutant were impaired in these processes (Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…During foot formation, it is hypothesized that the Brassicaceae-specific compatible pollen recognition occurs, although the full mechanism is not yet clearly understood (Hulskamp et al 1995;Pruitt 1999). There are two stigma-specific Brassica oleracea glycoproteins that play a role in this; S-Locus Glyco-protein and S-Locus Related1 (SLR1) (Luu et al 1997;Luu et al 1999) which may interact with two pollen coat specific proteins, PCP-A1 and SLR1-BP, respectively (Doughty et al 1998;Takayama et al 2000;Wang et al 2017). At this same moment, self-incompatible pollen grains can be recognized and deactivation of the basal pollen response beings while simultaneously activating the self-incompatibility signaling pathway (for review see, (Dresselhaus and Franklin-Tong 2013;Sawada et al 2014).…”
Section: Introductionmentioning
confidence: 99%